MELIHAT RASA DALAM KARYA LUKIS DONA PRAWIRA ARISUTTA - NOVRIDA PRATIWI (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2017)
This articel describes about the importance of taste and methaphors to make an artwork. This notion will be explained through Dona Prawira Arisutta’s artwork.  Dona is an artist who work with combine two different art, painting, and ceramic. That thecnique make an unusual thing for her artwork and become special. Dona’s artworks talk about taste, we can see it from her painting titled “The Tought”. This painting exhibited in Langit Art Space, Yogyakarta. That exhibition titled is “Urip Mung Mampir Ngumbe” also followed with famous artist. In Dona’s painting, she uses her intuition to make a methaphore from the objects of her painting